Biomedical signal processing methods for neuromarketing: A comparative study - SABAN, Suzan; DAĞDEVİR, Eda (International Conference on Applied Engineering and Natural Sciences, 2023)
Neuromarketing involves the integration of neuropsychology into marketing research, focusing on analyzing consumer sensory-motor actions, including cognitive and emotional responses to marketing stimuli, using advanced technologies. It represents one of the latest strategies in marketing research and has the potential to shape the future of the field. Numerous studies have already been conducted in this domain to enhance research outcomes. Nevertheless, the literature indicates that there are still opportunities for further advancements and improvements. A literature review was conducted in this article to explore the availability of an openly accessible dataset widely utilized by researchers in the field of neuromarketing. We examined the signal preprocessing, feature selection, feature extraction, and classification methods employed in studies utilizing the dataset created by Yadava et al.